2007
DOI: 10.1074/jbc.m702045200
|View full text |Cite
|
Sign up to set email alerts
|

The Selective RNA-binding Protein Quaking I (QKI) Is Necessary and Sufficient for Promoting Oligodendroglia Differentiation

Abstract: Quaking I (QKI) is a selective RNA-binding protein essential for myelination of the central nervous system. Three QKI isoforms with distinct C termini and subcellular localization, namely QKI-5, QKI-6, and QKI-7, are expressed in oligodendroglia progenitor cells (OPCs) prior to the initiation of myelin formation and implicated in promoting oligodendrocyte lineage development. However, the functional requirement for each QKI isoform and the mechanisms by which QKI isoforms govern OPC development still remain el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 44 publications
4
53
0
1
Order By: Relevance
“…2 E and F). Furthermore, the selective RNA-binding protein QKI that performs critical functions in promoting OL differentiation and myelination (20) was also significantly reduced in PIKE −/− mice ( Fig. 2 E and F), consistent with the previous report that QKI is a target of mTOR during OPC differentiation (21).…”
Section: Pike-l Is Required For Maintaining Akt/mtor Signaling Duringsupporting
confidence: 79%
“…2 E and F). Furthermore, the selective RNA-binding protein QKI that performs critical functions in promoting OL differentiation and myelination (20) was also significantly reduced in PIKE −/− mice ( Fig. 2 E and F), consistent with the previous report that QKI is a target of mTOR during OPC differentiation (21).…”
Section: Pike-l Is Required For Maintaining Akt/mtor Signaling Duringsupporting
confidence: 79%
“…Using an autosomal recessive mutant (qkv) model, the dysfunction of the mouse QKI gene has been well described as related to body tremor and the severe demyelination of the central nervous system [25]. To date, an increasing number of studies have confirmed that the human QKI gene in the brain plays a fundamental role in myelination and ODC differentiation [26,27]. Abnormal QKI expression may be critical in influencing other myelin-associated gene expression abnormalities in psychiatric disorders, such as schizophrenia and MDD.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of MS-CSF reactivity to quaking protein is potentially an important finding, given that the 37 kDa isoform has been shown to be essential for the development of oligodendrocyte progenitor cells by regulating their gene expression toward a promyelinating phenotype (77). Similarly, HSP-70 is required for the optimal expression of MBP (78), with HSP-70 also found to be associated with MBP in MS lesions, in an ATP-dependent fashion (79).…”
Section: Role Of Stress Proteins and Oligodendrocyte And Myelin Protementioning
confidence: 99%